ӨЗБЕК-ХАН БИЛІГІ КЕЗІНДЕГІ АЛТЫН ОРДАНЫҢ СЫРТҚЫ САЯСАТЫ. - Абдимомынов, Н. Т. (Journal of Oriental Studies, 2016)
В статье на основе средневековых источниках,раскрывается внешняя политика Золотой Орды в годыправление Узбек хана. Автор характеризирует цель изначение внешняя политика Узбек хана в рекон-струкции политических событий в начале ХІV в.In this article on the basis of medieval Arabian andPersian sources, is considered the foreign policy of theGolden Horde during the reign of Uzbek khan. The authorexplains the purpose and value foreign policy the Uzbek ofthe khan in reconstruction of political events beginning ХІVcentury.